2001
DOI: 10.1038/sj.bjp.0704409
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A and B evoke noradrenaline release from rat cerebrocortical slices

Abstract: 1 Orexin A and B, recently identi®ed in the rat hypothalamus are endogenous neuropeptide agonists for the G-protein coupled orexin-1 (OX1) and orexin-2 (OX2) receptors. 2 In the present study, we have examined the eects of orexin A, B and raised extracellular K + on noradrenaline release from the rat cerebrocortical slice. We have compared this with other sleep ± wake-related (excitatory) neurotransmitters; dopamine, glutamate, serotonin and histamine. 3 Neurotransmitter release studies were performed in rat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
(39 reference statements)
4
33
2
Order By: Relevance
“…HCRT-immunoreactive fibers and Hcrtr 1 are present in the LC (Marcus et al, 2001). Several lines of evidence have shown that HCRT excites LC neurons (Hagan et al, 1999;Horvath et al, 1999;Soffin et al, 2002;van den Pol et al, 2002) and induces NA release from their axonal terminals in the cerebral cortex and hippocampus (Hirota et al, 2001;Walling et al, 2004). Our present data demonstrated that HCRT at high concentration (1 M) is a trigger for NA secretion from the somatodendritic region.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…HCRT-immunoreactive fibers and Hcrtr 1 are present in the LC (Marcus et al, 2001). Several lines of evidence have shown that HCRT excites LC neurons (Hagan et al, 1999;Horvath et al, 1999;Soffin et al, 2002;van den Pol et al, 2002) and induces NA release from their axonal terminals in the cerebral cortex and hippocampus (Hirota et al, 2001;Walling et al, 2004). Our present data demonstrated that HCRT at high concentration (1 M) is a trigger for NA secretion from the somatodendritic region.…”
Section: Discussionsupporting
confidence: 53%
“…Our present data demonstrated that HCRT at high concentration (1 M) is a trigger for NA secretion from the somatodendritic region. These results imply that the projection from HCRT neurons to the LC may provide a pathway for HCRT modulation of LC functions, not only by regulating noradrenergic input to its targets (Hirota et al, 2001;Walling et al, 2004), but also by regulating noradrenergic transmission in its somatodendritic region. On the other hand, NMDA-type glutamate receptors are one of the major excitatory regulators of activity in LC neurons (Rasmussen, 1995).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Orexins have no direct effect on VLPO neurons, but the VLPO region contains numerous orexin fibers (Chou et al 2002). We speculate that orexins act presynaptically in the VLPO region to promote release of monoamines or ACh as has been demonstrated with NE release in the cortex (Hirota et al 2001). Alternatively, orexins may enhance monoaminergic inhibition of the VLPO by reducing reuptake of monoamines.…”
Section: Integration With Current Neurophysiologymentioning
confidence: 59%
“…Human variants of OX 1 and OX 2 receptors share a 64% sequence identity. Many studies suggest Ca 2ϩ influx as the most immediate cellular response to orexin receptor activation in different systems (van den Pol et al, 1998(van den Pol et al, , 1999Lund et al, 2000;Hirota et al, 2001;Kukkonen and Åkerman, 2001;Uramura et al, 2001;Holmqvist et al, 2002). This Ca 2ϩ influx may in some systems occur via protein kinase C-dependent activation of voltage-gated Ca 2ϩ channels (van den Pol et al, 1998;Uramura et al, 2001;Xu et al, 2002) but a different type of Ca 2ϩ channel has been implicated in other systems (Lund et al, 2000;Kukkonen and Åkerman, 2001).…”
mentioning
confidence: 99%